Unilateral vs. bilateral squat training for strength, sprints, and agility in academy rugby players - Speirs, D. E.; Bennett, M. A.; Finn, C. V.; Turner, A. P. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to investigate the effects of a 5-week lower-limb unilateral or bilateral strength program on measures of strength, sprinting, and change of direction speed. Eighteen academy rugby players (18.1 ± 0.5 years, 97.4 ± 11.3 kg, 183.7 ± 11.3 cm) were randomly assigned to either a unilateral (UNI) or bilateral (BI) group. The UNI group squatted exclusively with the rear elevated split squat (RESS), whereas the BI group trained only with the bilateral back squat (BS). Both groups trained at a relative percentage of the respective 1 repetition maximum (1RM) twice weekly over a 5-week period. Subjects were assessed at baseline and postintervention for 1RM BS, 1RM RESS, 10-m sprint, 40-m sprint, and pro-agility. There was a significant main effect of time for 1RM BS (F1,16 = 86.5, p < 0.001), ES (0.84 < Cohen d < 0.92), 1RM RESS (F1,16 = 133.0, p < 0.001), ES (0.89 < Cohen d < 0.94), 40-m sprint (F1,16 = 14.4, p = 0.002), ES (0.47 < Cohen d < 0.67) and pro-agility (F1,16 = 55.9, p < 0.001), ES (0.77 < Cohen d < 0.89), but not 10-m sprints (F1,16 = 2.69, p = 0.121), ES (0.14 < Cohen d < 0.38). No significant interactions between group and time were observed for any of the dependent variables. This is the first study to suggest that BI and UNI training interventions may be equally efficacious in improving measures of lower-body strength, 40-m speed, and change of direction in academy level rugby players.